Finding you [videorecording (DVD)] - Baugh, Brian; McNamara, Katherine; Redgrave, Vanessa, 1937-; Jackson, Saoirse-Monica; Scott, Tom Everett, 1970-; Goodacre, Jedidiah, 1989- (Roadside Attractions LLC, 2021)
Talented aspiring violinist Finley meets Beckett, a famous young movie star, on the way to her college semester abroad program in a small village in Ireland. An unexpected romance develops as the heartthrob Beckett leads the uptight Finley on an adventurous revival, and she inspires him to take charge of his future until the pressures of his stardom get in the way.